Implementasi Kebijakan Pemerintah Daerah dalam Pengelolaan Perkampungan Budaya Betawi Setu Babakan dalam Perspektif Hukum Tata Ruang - Muhammad Zaid Tsabit; Rahayu Subekti; Rosita Candrakirana (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study aims to analyze the implementation of local government policies in the management of the Setu Babakan Betawi Cultural Village from the perspective of spatial planning law. The research method employed is empirical legal research with a descriptive nature and a qualitative approach, involving document studies and interviews. The results show that the policy implementation has been carried out through various regulations; however, it still faces challenges such as fragmented authority among agencies, lack of coordination, and limited resources. To optimize the management and preservation of the area, strategic efforts are needed, including strengthening regulations, preparing a Detailed Spatial Plan (RDTR), increasing resources and budget allocation, involving the local community, and utilizing technology. Through these measures, the Setu Babakan Betawi Cultural Village is expected to remain a sustainable center for cultural preservation amidst Jakarta’s urban development.